Establishment of Small Medium Enterprise (SMEs) at Babussalam Al-Firdaus Islamic Boarding School, Karangploso, Malang - Nurcholis, Mochamad; Zubaidah, Elok; Putri, Widya Dwi Rukmi; Nur, Mokhamad; Hasna, Tanalyna; Putri, Aldila (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2022)
To overcome these problems, our team, initiate the establishment of SMEs involving students at the Babussalam Al-Firdaus Islamic Boarding School through diversification of dairy-based processed products and bakery products. Introduction of some lectures including bakery products technology, milk processing technology, packaging and storage technology, food quality assurance and Good Manufacturing Practice (GMP), product trials and training activities are carried out offline at the Food Production and Training Center (FPTC), Universitas Brawijaya. The new SMEs empowerment of students and provide additional income for the Babussalam Al-Firdaus Islamic Boarding School to be financial independence.